Kenyamanan Termal Melalui Inovasi Penangkap Angin dan Air Untuk Bangunan diperkotaan - Sidi Ahyar Wiraguna (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2024)
Thermal comfort is a crucial aspect that affects the quality of life and productivity of urban building occupants. This research aims to evaluate the effectiveness of wind capture systems and water use in improving thermal comfort in urban buildings in Indonesia. The research combines qualitative and quantitative methods with a desk study approach and expert interviews to gain an in-depth understanding of the application of these wind catchers in the local context. The scope of the research includes analyzing the design of wind catchers and water-based cooling systems and their impact on air circulation and temperature reduction inside buildings. Literature studies were used to identify theories and best practices, while expert interviews were conducted to gain practical insights into their application. The results show that wind capture systems are effective in improving air circulation and reducing indoor temperature, especially when the building design and orientation are aligned with the dominant wind direction. In addition, the use of a water-based cooling system was shown to significantly reduce indoor temperatures through the evaporation process, although it requires regular maintenance to maintain efficiency and prevent the growth of microorganisms. The conclusion of this study confirms that the integration of wind capture systems and water-based cooling systems can create an effective sustainable solution to improve thermal comfort in Indonesian urban buildings. This integration not only supports occupant comfort, but also contributes to the reduction of energy consumption and greenhouse gas emissions, in line with the development goals of green and sustainable buildings. Further research is recommended to develop design guidelines that are specific and customized to local climate conditions.